The collected early poems and plays - Duncan, Robert, 1919-1988 (Collected Writings of Robert Duncan., 2012)
A landmark in the publication of twentieth-century American poetry, this first volume of the long-awaited collected poetry, non-critical prose, and plays of Robert Duncan gathers all of Duncan's books and magazine publications up to and including Letters: Poems 1953-1956. Deftly edited, it thoroughly documents the first phase of Duncan's distinguished life in writing, making it possible to trace the poet's development as he approaches the brilliant work of his middle period. This volume includes the celebrated works Medieval Scenes and The Venice Poem, all of Duncan's long.